Effects of family planning educational intervention packages on oral contraceptive use in Rajchaburi, Thailand. - Gidchawan, Yowvapa (Thesis (DrPH) - University of the Philippines Manila, 1993)
Oral contraceptive (OC) is a major component of the National Family Planning program (NFPP) of Thailand. The decline in the prevalence of its use during the past caused by the side effects, has brought about a government policy aimed at enhancing continuance of OC. Non-compliance of OC regimen can lead to both indirectly to more frequent side effects and consequently discontinuation and directly to unplanned pregnancy. The purpose of the study is to measure the effectiveness of three Family Planning (FP) educational intervention in enhancing OC compliance and continuance of OC use by determining 1)the effects of FP educational intervention package in terms of changes in FP KAP, compliance to OC regimen, and continuous use, and 2)and interpretive mathematical model for predicting the relationship between client's compliance to OC regimen and continuous use; and the independent variables.
Three FP educational interventions, namely: (1) an exit interview together with a series of small group discussions; and (3)an exit interview and printed matters together with home visits; were provided to clients who were starting to use OC and who continued using the method during the return visits. Clients at the Provincial Hospital served as a control group and obtained the usual routine OC service; while those at MCH centers served as the experimental groups and were assigned randomly to three (3)groups of FP educational interventions. There was a total of 265 subjects which were distributed to the three experimental with group 1 having of 65, group 2, 77, and group 3, 59 subjects; while the control group had 64 subjects. independent variables.
Three (3) indicators were employed to determine the effectiveness of FP educational intervention, namely: (1)FP KAP; (2) Compliance to OC regimen; and (3) OC continuous use. The baseline data on KAP interview was conducted to new OC acceptors of FP clinic. Client's OC compliance and continuance were assessed through the review of the Follow-up Attendance Record at every quarter of the follow-up period. Post intervention KAP interview was determined after 12 months of OC acceptance by using identical questionnaire. Two trained research assistants were responsible for the sampling, KAP interview, providing FP educational intervention, and collecting data on pill practice of both FP clinics
Data on FP KAP were measured by comparing the relative difference in percent between the pretest and post-test difference and dividing the differences with percentage of the post-test, multiplied by 100. A score developed by giving weight to the more important behaviors of pill practice was used to measure the client?s compliance to OC regimen. The first method continuation rate of the client?s OC use by dividing the number of clients who were still using OC by the number of clients who accepted OC at the end of a given period of time. Oneway ANOVA was used to determine the changes in FPKAP, the difference of FPKAP, OC compliance, and continuous use between the three experimental groups. Multiple regression analysis through the use of dummy variables was employed to determine the relationship between OC compliance as well as continuous use and independent variables in the form of the interpretative mathematical model.
Most of the clients in the experimental groups were at high risk of unplanned pregnancy and discontinuation of OC in terms of their early age at marriage, low education and income, having latest child of less than 6 months, having 2-3 children, and residing in rural areas; compared to those in the control group who married late, had higher education and income, had 1-2 living children, and living in urban areas.
FP knowledge prior to the study among the three experimental groups was lower than the control group, but increased significantly to be as high as the control group at the post-test. There was no significant increase in FP favorable attitudes and practice in the three experimental groups compared with a significant increase in the control group, although the difference between the experimental and the control groups was not significant. Most of the clients in all 4 groups complied to OC regimen and there was no significant difference in OC compliance score among the three experimental groups. Clients in all 4 groups shared similar experiences of OC side effects and complications. Though OC continuation rate at 12 months of the acceptance was highest in the control group, data revealed that those who discontinued OC particularly in the experimental groups were using other less self-administration and long-term effect contraceptive methods.
Age at first marriage, education, income level, FPKAP and quality of FP services were predictive variables of both compliance to OC regimen and OC continuous use. Compliance to OC regimen was another significant predictor of OC continuous use.
The exit interview and printed matters was the most effective educational intervention package in bringing about compliance to OC regimen and OC continuous use among clients who were at high risk of unplanned pregnancy and discontinuation. Family planning programs, IEC materials, and educational intervention should be designed, implemented, and evaluated to make certain that they are effective. The lifestyles of the target population and the influence of the significant others should be considered in planning the programs. Further research on the socio-cultural characteristics and life styles among rural and urban users and non-users will provide valid data for planning effective FP programs. Evaluation on the utilization of IEC materials among various groups of clients will guide the decisions of health planners in designing appropriate IEC materials. Training in educational strategies and updated contraceptive methods should be regularly conducted for health care providers.
Keywords: Family planning; Oral contraceptive